2011
DOI: 10.1111/j.1349-7006.2011.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of a newly identified laminin, laminin‐3B11, in vascular basement membranes of invasive human breast cancers

Abstract: Laminins present in the basement membranes (BM) of blood vessels are involved in angiogenesis and other vascular functions that are critical for tumor growth and metastasis. Two major vascular laminins, the a4 (laminin-411 ⁄ 421) and a5 (laminin-511 ⁄ 521) types, have been well characterized. We recently found a third type of vascular laminin, laminin-3B11, consisting of the a3B, b1 and c1 chains, and revealed its biological activity. Laminin-3B11 potently stimulates vascular endothelial cells to extend lamell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…These structural and functional changes of blood vessels are thought to have significant effects on tumor growth and metastasis. Recently we found that a novel form of laminin, laminin‐3B11, is present in the vascular basement membranes of various normal tissues, but its expression is lost in cancer tissues . Both AGM and laminin‐3B11 are cell adhesion ligands assembled into the basement membrane structure, but their expression patterns are completely opposite as shown in this and previous studies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These structural and functional changes of blood vessels are thought to have significant effects on tumor growth and metastasis. Recently we found that a novel form of laminin, laminin‐3B11, is present in the vascular basement membranes of various normal tissues, but its expression is lost in cancer tissues . Both AGM and laminin‐3B11 are cell adhesion ligands assembled into the basement membrane structure, but their expression patterns are completely opposite as shown in this and previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…Five‐ μ m serial frozen sections were obtained from (KCRIA) and subjected to immunohistochemistry as described previously . The sections were treated with the first antibody, biotin‐conjugated second antibody (Vector; CA) and then streptoavidin‐conjugated peroxidase (Vector).…”
Section: Methodsmentioning
confidence: 99%
“…Five-lm serial frozen sections were obtained from KCRIA and subjected to immunohistochemistry as described previously. (25) The sections were treated with the first antibody, biotin-conjugated second antibody (Vector, Burlingame, CA, USA) and then streptoavidin-conjugated peroxidase (Vector). The resultant immunocomplexes were visualized with 3,3-diaminobenzidine (DAB) using the Histofine kit (Nichirei, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Five‐μm serial frozen sections were obtained from KCRIA and subjected to immunohistochemistry as described previously . The sections were treated with the first antibody, biotin‐conjugated second antibody (Vector, Burlingame, CA, USA) and then streptoavidin‐conjugated peroxidase (Vector).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Lm111 is modified by ectokinases secreted by immune cells during extravasation, which alters the properties of the EC-BM barrier ( 46 ). In breast carcinomas, pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α, suppress laminin α3B (LAMA3B) but enhances LAMA4 expression ( 47 ). In the breast tumors this changes the highly crosslinked and organized LAMA3B-rich EC-BM structure of the mammary gland ( 48 ) to a highly dynamic LAMA4-rich structure.…”
Section: Changes In the Endothelial Cell Basement Membrane Associatedmentioning
confidence: 99%